Pelatihan Bisnis Afiliasi Tiktok Pada Karang Taruna Desa Negeri Agung Ogan Komering Ulu Selatan - Defi Pujianto; Kadarsih Kadarsih; Dina Novriani; Bella Okta Vona; Enjel Lita Yuni Lestari; Agung Bayu Kesuma; Fajar Ardi Apsyari (Pusat Riset dan Inovasi Nasional, 2023)
The tiktok application is a social media with the main video content. This social media provides affiliate features for business needs. The purpose of this Community Service is to provide training to young people from the village of Negeri Agung cadets to use the Tik-Tock affiliate feature as a place to earn income from the internet. The service method is carried out by providing practical training offline by registering a TikTok account as an affiliate. As a result of this community service, village youth youth organizations have a tiktok affiliate account and increase youth knowledge of the business opportunities for social media tiktok affiliates. This dedication activity also provides additional income opportunities that come from the TikTok affiliate business.